A avaliação na educação infantil: perspectivas teórico-práticas - Drape, Renata Aparecida (2019)
In the last decades, early childhood education has been expanding, besides being solid in the context of formal education, it has also been presented as a target of government programs and actions, guiding documents and guidance materials aimed at ensuring the rights of young children. Although in recent years we have observed a remarkable increase in the number not always accompanied by high quality standards, early childhood education in Brazil has faced many controversial issues, including the evaluation that appears as the theme of this research project. The evaluation is a theme that presents a considerable range of of places in kindergarten, considering the data from the School Census presented by the National Institute of Studies and Research Anísio Teixeira (INEP), pointing to an 11.1% growth in the number of enrolments In early childhood education from 2014 to 2018, this expansion cannot yet be considered sufficient to meet the demand of different Brazilian states. We should also consider that this expansion is strongly evident in preschool over kindergarten, indicating that the discrepancy between the stages has not yet been overcome despite the development of broader public policies. Thus, marked by a context of quantitative expansion, but conceptions that unfold in different evaluative practices and the present work intends to investigate the conception of evaluation of the managers and teachers of the kindergarten of the municipal network of the city of São Carlos-SP. From a qualitative point of view, it is based on the methodology of the policy cycle approach, as we see the importance of considering the policy from its production (at the macro level) to its interpretation and application (in micro contexts, such as the Municipalities). To this end, the research sought to be based on bibliographic, documentary and field research that took place through semi-structured interviews with the educational supervisor and the presidents of the Municipal Education Council of the bienniums 2016-2018 and 2018-2020, and the realization focus group methodology with the kindergarten teachers of the municipal network. We conclude from the data obtained through this research that the continuing education of teachers working in municipal early childhood education is necessary and urgent. In addition, the municipal network of São Carlos (counselors, directors, teachers and community) presents the need for the appropriation of knowledge in the area of early childhood education, and especially in the evaluation theme, which enable the creation, implementation and management (jointly) concatenated actions that are part of an educational public policy whose main objective is the integral development of the child and to secure such right.